Intravenous Infusion of Dexmedetomidine Combined Isoflurane Inhalation Reduces Oxidative Stress and Potentiates Hypoxia Pulmonary Vasoconstriction during One-Lung Ventilation in Patients - Rui Xia; Jinjin Xu; Hong Yin; Huozhi Wu; Zhengyuan Xia; Daiwei Zhou; Zhong-yuan Xia; Liangqing Zhang; Haobo Li; Xiaoshan Xiao (Hindawi Limited, 2015)
Inhalation anesthetic isoflurane inhibits hypoxia pulmonary vasoconstriction (HPV), while dexmedetomidine (Dex) could reduce the dose of isoflurane inhalation and potentiate HPV, but the mechanism is unclear. Inhibition of reactive oxygen species (ROS) production can favor HPV during one-lung ventilation (OLV). Similarly, nitric oxide (NO), an important endothelium-derived vasodilator in lung circulation, can decrease the regional pulmonary vascular resistance of ventilated lung and reduce intrapulmonary shunting. We hypothesized that Dex may augment HPV and improve oxygenation during OLV through inhibiting oxidative stress and increasing NO release. Patients undergoing OLV during elective thoracic surgery were randomly allocated to either isoflurane + saline (NISO, n=24) or isoflurane + dexmedetomidine (DISO, n=25) group. Anesthesia was maintained with intravenous remifentanil and inhalational isoflurane (1.0-2.0%), with concomitant infusion of dexmedetomidine 0.7 μgkg−1h−1 in DISO and saline 0.25 mL kg−1h−1 in NISO group. Hemodynamic variables or depth of anesthesia did not significantly differ between groups. Administration of Dex significantly reduced Qs/Qt and increased PaO2 after OLV, accompanied with reduced lipid peroxidation product malondialdehyde and higher levels of SOD activity as well as serum NO (all P<0.05 DISO versus NISO). In conclusion, reducing oxidative stress and increasing NO release during OLV may represent a mechanism whereby Dex potentiates HPV.